Завдання контуру стратегічного управління ефективністю бізнес-процесів в організації - Romanenkov, Yu. А.; Zieiniiev, T. G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The publication is devoted to comprehensive study of internal company factors and patterns, while directly forming stable competitive strengths and influencing the company strategy. A scheme of the structure of the strategic management of business process performance in a company based on the optimization mechanism for generating strategies has been proposed. The problems of structure of strategic management have been established, herewith these problems require further formalization within the framework of the management scheme being offered, namely: a task of monitoring the external environment, a task of estimation system’s response time; synthesis and analysis tasks, a task of forecasting support of management decision making; a task of providing with means of information support for management decision making; a task of risk evaluation for implementing management decisions under conditions of uncertainty.